Finite-time cooperative control strategies for the economic operation of hybrid AC/DC microgrids - Martinez Gomez, Manuel (2024)
This work focuses on developing a distributed control strategy that guarantees optimal and stable operation of multiple interconnected AC/DC hybrid microgrids. The strategy's application focuses on the isolated operation of low-voltage microgrids with distributed generators (DGs) based on renewable energy sources with power converters for interconnection and control. For the interconnection between microgrids, interlinking converters (ILCs) are used. The studied system is divided into parts in order to facilitate the analysis of the control proposals, among them are: (i) AC/DC microgrid with an ILC, (ii) AC/DC micro-grid with a cluster of multiple ILCs, and (iii) multi-microgrid AC/DC with clusters of ILCs. The proposed control scheme is distributed and cooperative and is implemented in the ILCs. This scheme is designed to be compatible with the actions of secondary and tertiary control (economic dispatch) of the adjacent DGs. Each controller incorporates finite-time consensus algorithms to improve transient states; in addition, they use marginal generation cost variables. Additionally, a multipurpose controller is proposed for each ILC with the ability to incorporate control actions that safeguard the saturated operation of microgrids, balance the power between ILCs in the same cluster, and avoid the saturated operation of clusters of ILCs. The contributions of this doctoral thesis can be summarised as follows: (i) the formulation of a multi-objective strategy for hybrid AC/DC microgrids and AC/DC multi-microgrids that have clusters of ILCs. The formulation considers as an objective function the combination of economic dispatch, power balance within a cluster of ILCs, and penalty functions to avoid the saturated operation of microgrids and clusters of ILCs; (ii) the design of cooperative distributed controllers for the ILCs based on the incremental cost, average power of the microgrids, and average power of the ILC cluster; (iii) the inclusion of improvements for convergence through the tuning of finite-time algorithms, which allow economic dispatch to be executed on a time scale equivalent to that of secondary control; (iv) the development of an anti-windup method to reduce the effect of delays in communication links for a moving average consensus algorithm; (v) the experimental development of part of an AC/DC hybrid microgrid test bench prototype. The experimental and simulation results show an adequate response of the proposed multi-objective controller, allowing global optimal dispatch in AC/DC microgrids and AC/DC multi-microgrids while taking care not to overload DGs, ILCs, subgrids, and clusters of ILCs. The simultaneous operation of the control actions of the proposed objectives is possible due to the control parameters designed to adjust the prioritisation. Thanks to the incorporation of anti-windup, steady-state errors can be reduced, and thus it is possible to operate against considerable time delays.